The [72,36] Type 11 Self Dual Codes from Hadamard Matrices - Rowena Baylon-Cabrizos (Davao Research Journal)
Consider a code [n,k,d] of length n, dimension k and of minimum distance d. Let R be a rate defined by the equation R = k/n. Mathematically, the main problem of coding theory is to find codes with large R (for efficiency) and large d (to correct many errors). This paper diseuses the binary [72,36] code constructed from Hadamard matrices.